Orientalism - Said, Edward W (Tornoto Vintage Books, 1994)
The theme is the way in which intellectual traditions are created and transmitted ... Orientalism is the example Mr. Said uses, and by it he means something precise. The scholar who studies the Orient (and specifically the Muslim Orient), the imaginitive writer who takes it as his subject, and the institutions which have been concerned with teaching it, settling it, ruling it, all have a certain representation or idea of the Orient defined as being other than the Occident, mysterious, unchanging and ultimately inferior."--Albert Houran -- from http://www.amazon.com (Jan. 28, 2014).
Keywords: East and West -- Imperialism -- Asia -- Education -- Middle East -- Public opinion, Western -- Foreign public opinion, Occidental